2012
DOI: 10.1111/j.2042-7158.2011.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonist pioglitazone improves scopolamine-induced memory impairment in mice

Abstract: Pioglitazone demonstrates a significant neuroprotective effect against scopolamine-induced cholinergic system deficit and cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Substance P may decrease the level of PPAR c that reduces the protective effect of PPAR c on survival of neurons. PPAR-c decreases the level of proinflammatory mediators (Clark 2002), increases the development and growth of brain size, and increases the level of choline acetyltransferase (ChAT) expression (Xiang et al 2012). ChAT modulates synthesis and formation of acetylcholine by catalyzing the transfer of an acetyl group from the acetyl-CoA to choline yielding acetylcholine (ACh) (Kim et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Substance P may decrease the level of PPAR c that reduces the protective effect of PPAR c on survival of neurons. PPAR-c decreases the level of proinflammatory mediators (Clark 2002), increases the development and growth of brain size, and increases the level of choline acetyltransferase (ChAT) expression (Xiang et al 2012). ChAT modulates synthesis and formation of acetylcholine by catalyzing the transfer of an acetyl group from the acetyl-CoA to choline yielding acetylcholine (ACh) (Kim et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“… 2012 ; Xiang et al. 2012 ) at a dose of 0.1 mg/kg intraperitoneally (Kay et al. 2010 ); (3), (4), and (5) L. officinalis extract-pretreated groups received L. officinalis extract with concentrations of 100, 200 and 400 mg/kg (Kashani et al.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroprotective effects of the PPARg agonists rosiglitazone, pioglitazone, and 15-deoxy-prostaglandin J 2 were reported in studies of animal models of ischemic stroke (Bordet et al, 2006;Culman et al, 2007). It was shown that long-term treatment with pioglitazone improved cognitive deficits and AD-related pathology in a mouse model of AD (Sato et al, 2011;Gupta and Gupta, 2012;Searcy et al, 2012;Xiang et al, 2012). Neuroprotective effects of PPAR agonists have also been demonstrated in experimental models of PD (Chaturvedi and Beal, 2008;Ridder and Schwaninger, 2012).…”
mentioning
confidence: 89%